The Role of Team Cohesion in Success: A Literature Review from a Psychological Perspective - Mehdi Abadi, Parichehr (Health Nexus, 2023)
This article presents a comprehensive literature review on the role of team cohesion in success, focusing on psychological perspectives. It explores theoretical frameworks, including definitions, models, and components of team cohesion, alongside factors influencing it at individual, team, and environmental levels. The review synthesizes empirical evidence on the impact of team cohesion on performance, discusses strategies for enhancing cohesion, and highlights the challenges involved. Future research directions and practical implications for leaders, organizations, and researchers are proposed, emphasizing the importance of understanding and leveraging team cohesion for optimizing performance in various contexts.